2002
DOI: 10.1046/j.1365-2648.2002.02179.x
|View full text |Cite
|
Sign up to set email alerts
|

SHORT REPORT: Nursing education in Norway

Abstract: There are many possibilities to improve nursing education in Norway. We are on our way with highly qualified teachers and students, and we still have enough good applicants. The new general plan and new law for universities and university colleges offer great opportunities. However, the shortage of nurses is a great challenge for further quality improvement both in clinical practice and in education.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 5 publications
(5 reference statements)
0
22
0
Order By: Relevance
“…The Norwegian nursing education is a 3-years bachelor program (180 ECTS) [33]. Further in the article we refer to them as registered nurses (RN).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Norwegian nursing education is a 3-years bachelor program (180 ECTS) [33]. Further in the article we refer to them as registered nurses (RN).…”
Section: Methodsmentioning
confidence: 99%
“…Education which provides specialist expertise in nursing is done by universities and university colleges and leads in some cases to a master’s degree. The program takes from 1 to 2 years fulltime (referred as specialist nurses) [33]. We also included the nurses that were not always directly involved in patient care, such as senior charge nurses and professional development nurses at the hospital units, as support from nursing administrators and leaders, is seen as a key element to promote EBP [34].…”
Section: Methodsmentioning
confidence: 99%
“…Studies dealing with nursing education reforms in Europe indicate that countries have learned very little from the reform process and that almost every country is repeating the past mistakes of others (26,28,33,34). Few reports exist describing the various reform processes or their outcomes.…”
Section: In Search Of a Croatian Concept Of Nursing Educationmentioning
confidence: 99%
“…The proponents of the first option argue that becoming a competent professional is a lifelong learning process; thus, rather than concentrating on exhaustive detailed knowledge and specific competencies, education should provide the basic cognitive tools to support lifelong learning processes. Therefore, graduates should have a strong and broad intellectual base, which would give them the necessary flexibility and adaptability (33,37).…”
Section: Outcome Profile and Competenciesmentioning
confidence: 99%
“…This is where students learn theory for a block of four to six weeks that is followed by clinical area placements for a period of six months. Studies done by [4,5] indicated that students were more satisfied with clinical practice than with the theoretical part of nursing program. Consequently [6] argued that despite the quality of education offered, excellence in customer service is the most important factor in determining the success of a learning program.…”
Section: Introductionmentioning
confidence: 99%